Composição química e avaliação termo-oxidativa do óleo das sementes de Couroupita guianensis Aubl. por métodos de oxidação acelerada - Silva, Maria Alcilene Alexandre Dantas da (2011)
Couroupita guianensis Aubl., popularly known as couroupita and/or apricot monkey, is a plant native to the Amazon region, but adaptable to other Brazilian regions. It is a species of the Lecitidáceae family, of which the Brazil nut also belongs. C. guianensis sufficiently is used in the Region North of Brazil in the treatments of the hipertention and antiinflammatory processes in general, in the form of teas and infusions. The centesimal composition of the seeds of couroupita determined in this work supplied 33,7% of lipids, 26,6% of proteins, 8,0% of humidity and 6,9% of ashes. Among the minerals studied, the most abundant were boron (18,20 mg.100-1g), followed by sodium (8,88 mg.100-1g), iron (5,93 mg.100-1g) and zinc (4,94 mg.100-1g). The selenium content (0,16 mg.100-1g) was slightly higher than those reported for Churu and Brazil nuts. The extracted oil of the seeds through the cold pressing mechanical extraction reached a 27% income w/w. Identification made by gaseous chromatography (GC) revealed a percentage of unsaturation of 85,6% with advantage of the linoleic acid (78,0%), followed of the oleic acid (8,8%). Evaluation of physico-chemical properties oil showed an acid value of 1,7% (% oleic acid), peroxide value of 2,0 mEq.Kg-1, iodine value (Wijs) of 121,6 g g I2 100 g-1; putting crude oil into the Brazilian specifications required for oils intended for food use. Thermal analysis of the oil determined by TG/DTG showed three stages of decomposition, with the first event occurring at 246° C, showing to be an oil of considerable thermal stability despite the high degree of unsaturation. The evaluation of oxidative stability of oil determined by the Rancimat technique showed an induction period (PI) considered of 4,7 h; by technique Pressurized Differential Scanning Calorimetry (PDSC), indicated an oxidative induction time (OIT) of 1,3 h and technical petroOxy an induction period of 2,2 h, expected values for oil with a high percentage of linoleic acid.